Anti-overcharge sodium ion battery and preparation method thereof
By using composite conductive agents in sodium ion batteries, a variety of conductive network forms are formed, and the internal resistance of the battery is reduced, the problem of overcharge failure of sodium ion batteries is solved, and the safety and performance of the battery are improved.
Patent Information
- Application Number
- CN202411539980.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-11
AI Technical Summary
Sodium ion batteries are prone to heat, deformation, liquid leakage and other problems during overcharging, resulting in reduced performance or damage, and even causing combustion or explosion. The existing technology lacks an effective method to solve the overcharge failure mechanism.
By using composite conductive agents in the positive and negative electrode materials of sodium ion batteries, including carbon black, carbon nanotubes and graphene, three conductive network forms are formed: point-point, point-line and point-face, to reduce the internal resistance of the battery and reduce the Joule heat generated during the charging and discharge process.
Effectively prevent sodium ion battery from overcharging and failure, improve battery safety, reduce temperature rise and battery impedance, and improve the performance and safety performance of sodium ion battery.
Smart Images

Figure CN119601753A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to an overcharge-proof sodium ion battery and a preparation method thereof. Background Art
[0002] The development of electronic technology has put forward a growing demand for the energy density, lifespan and fast charging performance of lithium-ion batteries for electronic products. However, the limited lithium reserves on the earth have kept the cost of lithium resources high, which has restricted the long-term development and application of lithium-ion batteries. Sodium-ion batteries, which have similar working principles to lithium-ion batteries, mainly use sodium salts as electrode materials, which are more abundant and cheaper than lithium salts. In addition, the chemical properties of sodium-ion batteries are relatively stable and safer, and are expected to be well applied in the fields of energy storage or low-speed new energy vehicles.
[0003] However, when sodium-ion batteries face some abuse conditions (such as overcharging), it is difficult to avoid generating heat and gas, which significantly reduces the performance and damages the battery. Especially during overcharging, it causes the internal pressure of the battery to increase, the battery to deform, and the battery to leak. In severe cases, it may even cause combustion or explosion, generate more heat, and cause battery failure. At present, there are few analytical reports on the failure mechanism of sodium-ion batteries due to overcharging, and there is also a lack of attention to the heat source and internal resistance changes during overcharging. Therefore, it is very important to reduce the overcharge temperature rise of sodium-ion batteries, which can provide guidance for improving the safety of sodium-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide an overcharge-proof sodium ion battery in response to the above technical problems, which reduces the internal resistance of the battery and generates less Joule heat during the charging and discharging process to prevent the sodium ion battery from overcharging and failure, thereby improving the safety of the battery.
[0005] The overcharge-proof sodium-ion battery in the technical solution of the present invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet comprises a current collector and a positive electrode material coated on the current collector. The negative electrode sheet comprises a current collector and a negative electrode material coated on the current collector. The positive electrode material comprises a positive electrode active material, a composite conductive agent and a positive electrode binder. The negative electrode material comprises a negative electrode active material, a composite conductive agent and a negative electrode binder. The composite conductive agent is two or more of carbon black, carbon nanotubes and graphene.
[0006] Preferably, the positive electrode active material includes but is not limited to one or more of sodium nickel iron manganate, sodium nickel cobalt manganate, sodium nickel iron titanate, sodium iron cobalt manganate, and sodium iron titanate manganate; preferably, the sodium nickel iron manganate ternary positive electrode material has both high voltage stability and high structural stability, which can slow down the phase change oxygen evolution and side reaction rate of the material during overcharging.
[0007] Furthermore, the mass percentages of the positive electrode active material, the conductive agent and the binder in the positive electrode material are 90-98%, 1.0-5.0% and 1.0-5.0% respectively.
[0008] Furthermore, the surface density of the positive electrode material coating is 15.0-20.0 mg / cm 2 , preferably 16.5 to 18.5 mg / cm 2 .
[0009] Furthermore, the mass percentages of the negative electrode active material, the composite conductive agent and the binder in the negative electrode material are 90-98%, 1.0-5.0% and 1.0-5.0% respectively.
[0010] Preferably, the negative electrode active material includes, but is not limited to, one or more of graphite, hard carbon, silicon, tin, phosphorus, and metal oxides.
[0011] Furthermore, the composite conductive agent is a mixture of carbon black, carbon nanotubes and graphene.
[0012] The carbon black in the composite conductive agent is in point-point contact form, the carbon black and carbon nanotubes are in point-line contact form, and the carbon black and graphene are in point-surface contact form. Selecting three different conductive network forms of point, line and surface at the same time can improve the conductive contact between the active material particles, reduce the electrode contact impedance, facilitate the transmission of sodium ions, and prevent overcharging. In addition, point-line contact and point-surface contact have good thermal conductivity, which is beneficial to heat dissipation, prevent battery overheating, and improve the safety performance of sodium ion batteries.
[0013] Furthermore, the mass percentages of the conductive carbon black, carbon nanotubes and graphene in the composite conductive agent are 40-60%, 20-30% and 20-30% respectively.
[0014] Furthermore, the surface density of the negative electrode material coating is 5.0 to 10.0 mg / cm 2 , preferably 6.5 to 8.5 mg / cm 2 .
[0015] Furthermore, the thickness of the current collector is 8 to 18 μm, preferably 10 to 15 μm.
[0016] Preferably, the current collector includes, but is not limited to, any one of aluminum foil, aluminum alloy sheet, copper foil, copper alloy sheet, nickel foil, nickel alloy sheet and stainless steel sheet.
[0017] Preferably, the positive electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride, polytetrafluoroethylene, and vinylidene fluoride-tetrafluoroethylene-propylene terpolymer resins.
[0018] Preferably, the negative electrode binder includes, but is not limited to, one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyvinyl alcohol, sodium alginate, polymethacrylic acid, sodium carboxymethyl cellulose and carboxymethyl chitosan.
[0019] Furthermore, the positive electrode sheet is prepared by adding positive electrode active material, positive electrode binder and conductive agent into an organic solvent to prepare slurry, coating the slurry on a current collector, and then drying, rolling and cutting the slurry.
[0020] Furthermore, the negative electrode sheet is prepared by adding negative electrode active material, negative electrode binder and composite conductive agent into an organic solvent to prepare slurry, coating the slurry on a current collector, and then drying, rolling and cutting the slurry.
[0021] Preferably, the drying temperature is 60-100° C. and the drying time is 6-10 hours.
[0022] Preferably, the roller pressing pressure is 5 to 8 MPa and the speed is 5 to 10 m / min.
[0023] Preferably, the organic solvent includes, but is not limited to, one or more of polyvinylpyrrolidone (PVP), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO); preferably, N-methylpyrrolidone.
[0024] The diaphragm and electrolyte in the present invention are not limited, and any diaphragm and electrolyte that can be used in sodium ion batteries can be used.
[0025] The present invention also provides a method for preparing the above-mentioned overcharge-proof sodium ion battery, comprising the following steps: forming a battery core with a positive electrode sheet, a negative electrode sheet and a diaphragm laminate, then welding a positive electrode tab and a negative electrode tab on the positive electrode sheet and the negative electrode sheet, placing the obtained battery core in an aluminum-plastic film shell for baking, injecting an electrolyte, sealing and allowing to stand for dissolving into a capacity, and then aging.
[0026] Furthermore, the positive electrode sheet, the negative electrode sheet and the separator are stacked in a Z-shaped manner.
[0027] Preferably, the baking temperature is 80-100° C. and the baking time is 24-48 hours.
[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0029] (1) By using a composite conductive agent to reduce the internal resistance of the battery and reduce the Joule heat generated during the charge and discharge process, the sodium ion battery can be prevented from overcharging and failure, thereby improving the safety of the battery and obtaining a sodium ion battery with good safety performance;
[0030] (2) Selecting three different conductive network forms of point, line and surface in the composite conductive agent can improve the conductive contact between the active material particles, reduce the electrode contact impedance, facilitate the transmission of sodium ions, and prevent overcharging;
[0031] (3) Point-line contact and point-surface contact have good thermal conductivity, which is beneficial to heat dissipation, can prevent battery overheating, and further improve the safety performance of sodium-ion batteries;
[0032] (4) The method for improving overcharging of sodium-ion batteries is simple and effective, and is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The voltage variation diagram of the sodium ion batteries obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below through specific examples and drawings. It should be understood that the specific examples described here are only used to help understand the present invention and are not used to specifically limit the present invention. The drawings used in this article are only for better illustrating the content disclosed by the present invention and do not have a limiting effect on the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the field, and the methods used in the embodiments are all conventional methods in the field. Example 1
[0035] The method for preparing a sodium ion battery in this embodiment comprises the following steps:
[0036] (1) 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and a composite conductive agent (1.5 parts of conductive carbon black, 1.0 parts of carbon nanotubes and 1.0 parts of graphene) were added to NMP to prepare a slurry at a temperature of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, rolled at a speed of 6 m / min under a pressure of 6 MPa, and cut to obtain a positive electrode sheet;
[0037] (2) 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and a composite conductive agent (1.0 parts of conductive carbon black, 0.5 parts of carbon nanotubes and 0.5 parts of graphene) were added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6 hours, and then rolled at a speed of 6m / min under a pressure of 6MPa, and cut to obtain the negative electrode sheet;
[0038] (3) The positive electrode sheet, the negative electrode sheet and the porous polypropylene separator are stacked in a Z-shape to form a battery cell, and then the positive electrode tab and the negative electrode tab are welded on the positive electrode sheet and the negative electrode sheet. The obtained battery cell is placed in an aluminum-plastic film shell and baked at 80°C for 24 hours, and the electrolyte is injected, sealed and left to stand for dissolution, and then aged.
[0039] Example 2
[0040] The method for preparing a sodium ion battery in this embodiment comprises the following steps:
[0041] (1) 96 parts of sodium nickel cobalt manganate, 1.0 part of polyvinylidene fluoride and a composite conductive agent (1.5 parts of conductive carbon black, 1.0 parts of carbon nanotubes and 1.0 parts of graphene) were added to NMP to prepare a slurry at 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, rolled at a speed of 6 m / min under a pressure of 6 MPa, and cut to obtain a positive electrode sheet;
[0042] (2) 94 parts of silicon-carbon composite material, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and composite conductive agent (1.0 parts of conductive carbon black, 0.5 parts of carbon nanotubes and 0.5 parts of graphene) were added to an organic solvent to prepare a slurry at a temperature of 8.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6 hours, and then rolled at a speed of 6m / min under a pressure of 6MPa, and cut to obtain the negative electrode sheet;
[0043] (3) The positive electrode sheet, the negative electrode sheet and the porous polypropylene separator are stacked in a Z-shape to form a battery cell, and then the positive electrode tab and the negative electrode tab are welded on the positive electrode sheet and the negative electrode sheet. The obtained battery cell is placed in an aluminum-plastic film shell and baked at 80°C for 24 hours, and the electrolyte is injected, sealed and left to stand for dissolution, and then aged.
[0044] Example 3
[0045] The method for preparing a sodium ion battery in this embodiment comprises the following steps:
[0046] (1) 95 parts of sodium iron cobalt manganate, 1.5 parts of polyvinylidene fluoride and a composite conductive agent (1.5 parts of conductive carbon black, 1.0 parts of carbon nanotubes and 1.0 parts of graphene) were added to NMP to prepare a slurry at 18.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, rolled at a speed of 6 m / min under a pressure of 6 MPa, and cut to obtain a positive electrode sheet;
[0047] (2) 95 parts of sodium titanate, 3.0 parts of carboxymethyl chitosan and a composite conductive agent (0.8 parts of conductive carbon black, 0.6 parts of carbon nanotubes and 0.6 parts of graphene) were added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6 hours, and then rolled at a speed of 6m / min under a pressure of 6MPa, and cut to obtain the negative electrode sheet;
[0048] (3) The positive electrode sheet, the negative electrode sheet and the porous polypropylene separator are stacked in a Z-shape to form a battery cell, and then the positive electrode tab and the negative electrode tab are welded on the positive electrode sheet and the negative electrode sheet. The obtained battery cell is placed in an aluminum-plastic film shell and baked at 80°C for 24 hours, and the electrolyte is injected, sealed and left to stand for dissolution, and then aged.
[0049] Example 4
[0050] The difference between this embodiment and embodiment 1 is that in step (1), 95 parts of sodium nickel iron manganate, 2.0 parts of polyvinylidene fluoride and a composite conductive agent (1.8 parts of conductive carbon black, 0.6 parts of carbon nanotubes and 0.6 parts of graphene) are added to NMP to prepare a slurry at a temperature of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0051] Example 5
[0052] The difference between this embodiment and embodiment 2 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and a composite conductive agent (0.8 parts of conductive carbon black, 0.6 parts of carbon nanotubes and 0.6 parts of graphene) are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then rolled and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0053] Example 6
[0054] The difference between this embodiment and embodiment 1 is that in step (1), 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and a composite conductive agent (2.0 parts of conductive carbon black and 1.5 parts of graphene) are added to NMP to prepare a slurry at a concentration of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0055] Example 7
[0056] The difference between this embodiment and embodiment 1 is that in step (1), 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and a composite conductive agent (2.0 parts of conductive carbon black and 1.5 parts of carbon nanotubes) are added to NMP to prepare a slurry at a concentration of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0057] Example 8
[0058] The difference between this embodiment and embodiment 1 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and a composite conductive agent (1.2 parts of conductive carbon black and 0.8 parts of graphene) are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then dried, rolled, and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0059] Example 9
[0060] The difference between this embodiment and embodiment 1 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and a composite conductive agent (1.2 parts of conductive carbon black and 0.8 parts of carbon nanotubes) are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then dried, rolled and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that in step (1), 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and 3.5 parts of conductive carbon black are added to NMP to prepare a slurry at a concentration of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that in step (1), 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and 3.5 parts of carbon nanotubes are added to NMP to prepare a slurry at a concentration of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0065] Comparative Example 3
[0066] The difference between this comparative example and Example 1 is that in step (1), 95 parts of sodium nickel iron manganese oxide, 1.5 parts of polyvinylidene fluoride and 3.5 parts of graphene are added to NMP to prepare a slurry at a temperature of 16.0 mg / cm 2 The surface density was coated on an aluminum foil with a thickness of 12 μm, dried at 80°C for 6 h, and then rolled and cut at a speed of 6 m / min under a pressure of 6 MPa to obtain a positive electrode sheet.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 1 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and 2.0 parts of conductive carbon black are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then rolled and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0069] Comparative Example 5
[0070] The difference between this comparative example and Example 1 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and 2.0 parts of carbon nanotubes are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then rolled and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0071] Comparative Example 6
[0072] The difference between this comparative example and Example 1 is that in step (2), 94 parts of hard carbon, 2.2 parts of sodium carboxymethyl cellulose, 1.8 parts of styrene-butadiene rubber and 2.0 parts of graphene are added to an organic solvent to prepare a slurry at a concentration of 6.0 mg / cm 2 The surface density of the film was coated on the current collector, dried at 80°C for 6h, and then rolled and cut at a speed of 6m / min under a pressure of 6MPa to obtain the negative electrode sheet.
[0073] The sodium ion batteries obtained in the above embodiments and comparative examples were charged at 0.1C constant current for 2h at 45°C, and then charged at 0.2C constant current for 4h; the capacity was charged at 0.5C constant current at 25°C to the cut-off voltage, and discharged at 0.5C constant current to the cut-off voltage, and then the capacity was screened; the aging was performed at 25°C for 24h;
[0074] Figure 1The voltage of the sodium ion batteries obtained in Example 1 and Comparative Example 1 is changed with the charging time when the battery is fully charged at 0.5C and charged to 1.5 times (5.9V) of the cut-off voltage (3.95V). It can be seen that the area formed by the voltage rise curve and time in Example 1 is obviously smaller, and the area formation is related to the voltage platform. The longer the voltage platform, the larger the area formed, which is proportional to the heat generation. It can be seen that the heat generation in Example 1 is smaller;
[0075] The temperature rise and impedance performance of the sodium ion battery were tested after it was charged at 0.5C to 1.5 times (5.9V) of the cut-off voltage (3.95V) when fully charged. The test results are shown in Table 1.
[0076] Table 1 Sodium ion battery performance data
[0077]
[0078]
[0079] In Examples 1-5, the positive and negative electrode conductive agents are combined in the form of three different conductive networks: points, lines, and surfaces, which reduces the Joule heat generated during the charge and discharge process, reduces the temperature rise and battery impedance, and obtains a sodium ion battery with good performance; in Examples 6-9, two conductive networks are combined in the positive electrode material or the negative electrode material, the conductivity is slightly weak, and the internal resistance of the sodium ion battery increases; in Comparative Examples 1-3, the positive electrode material only uses carbon black or carbon nanotubes or graphene as a conductive agent, and in Comparative Examples 4-6, the negative electrode material only uses carbon black or carbon nanotubes or graphene as a conductive agent, the conductive network structure is single, the difficulty of sodium ion transmission is increased, the battery temperature rise is significantly increased, the internal resistance is increased, and the conductivity and safety performance are reduced.
[0080] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. An overcharge-proof sodium ion battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes a current collector and a positive electrode material coated on the current collector. The negative electrode sheet includes a current collector and a negative electrode material coated on the current collector. The positive electrode material includes a positive electrode active material, a composite conductive agent and a positive electrode binder. The negative electrode material includes a negative electrode active material, a composite conductive agent and a negative electrode binder. The composite conductive agent is two or more of carbon black, carbon nanotubes and graphene.
2. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The mass percentages of the positive electrode active material, the conductive agent and the binder in the positive electrode material are 90-98%, 1.0-5.0% and 1.0-5.0% respectively.
3. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The surface density of the positive electrode material coating is 15.0-20.0 mg / cm 2 .
4. The overcharge-proof sodium ion battery according to claim 1, characterized in that: The mass percentages of the negative electrode active material, the composite conductive agent and the binder in the negative electrode material are 90-98%, 1.0-5.0% and 1.0-5.0% respectively.
5. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The composite conductive agent is a mixture of carbon black, carbon nanotubes and graphene.
6. The overcharge-proof sodium-ion battery according to claim 5, characterized in that: The mass percentages of conductive carbon black, carbon nanotubes and graphene in the composite conductive agent are 40-60%, 20-30% and 20-30% respectively.
7. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The surface density of the negative electrode material coating is 5.0-10.0 mg / cm 2 .
8. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The positive electrode sheet is prepared by adding positive electrode active material, positive electrode binder and conductive agent into an organic solvent to form a slurry, which is then coated on a current collector and dried, rolled and cut.
9. The overcharge-proof sodium-ion battery according to claim 1, characterized in that: The negative electrode sheet is prepared by adding negative electrode active material, negative electrode binder and composite conductive agent into an organic solvent to form a slurry, which is then coated on a current collector and dried, rolled and cut.
10. A method for preparing an overcharge-proof sodium ion battery according to claim 1, characterized in that: The method comprises the following steps: forming a battery cell with a positive electrode sheet, a negative electrode sheet and a diaphragm laminate, then welding a positive electrode tab and a negative electrode tab on the positive electrode sheet and the negative electrode sheet, placing the obtained battery cell in an aluminum-plastic film shell for baking, injecting electrolyte, sealing and standing to dissolve into the capacity, and then aging.